PENERAPAN KURIKULUM TINGKAT SATUAN PENIDDIKAN (KTSP) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH - Ahmad Zaki Mubarak (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
'Teachcrs are the key people for the success of KTSP curriculum implementation. This is'beiause teachers are the implanters of the curriculum